Determination of titanium atom and ion densities in sputter deposition plasmas by optical emission spectroscopy. (25th November 2015) - Vašina, P; Fekete, M; Hnilica, J; Klein, P; Dosoudilová, L; Dvořák, P; Navrátil, Z
Abstract: The thorough characterizations of deposition plasma lead to important achievements in the fundamental understanding of the deposition process, with a clear impact on the development of technology. Measurement of the spatial and, in the case of pulse excited plasma, also temporal evolution, of the concentrations of sputtered atoms and ions is a primary task in the diagnostics of any sputter deposition plasma. However, it is difficult to estimate absolute number densities of the sputtered species (atoms and ions) in ground states directly from optical emission spectroscopy, because the species in the ground levels do not produce any optical signal. A method using effective branching fractions enables us to determine the density of non-radiating species from the intensities of self-absorbed spectral lines. The branching fractions method described in the first part of this paper was applied to determine the ground state densities of the sputtered titanium atoms and ions. The method is based on fitting the theoretically calculated branching fractions to experimentally measured ratios of the relative intensities of carefully selected resonant titanium atomic and ionic lines. The sputtered species density is determined in our experimental setup with a relative uncertainty of less than 5% for the dc driven magnetron and typically 15% for time-resolved measurements of high-power impulse magnetron sputtering (HiPIMS) discharge. In the second part of the paper, the method was applied to determine the evolution of titanium atom and ion densities in three typical cases ranging from the dc driven sputter process to HiPIMS.